A Review of Possible EEG Markers of Abstraction, Attentiveness, and Memorisation in Cyber-Physical Systems for Special Education - Dimitrova, Maya; Wagatsuma, Hiroaki; Krastev, Aleksandar; Vrochidou, Eleni; Nunez-Gonzalez, J. David (Frontiers in Robotics and AI, 2021)
Cyber-physical systems (CPS) for special education rely on effective mental and brain processing during the lesson, performed with the assistance of humanoid robots. The improved diagnostic ability of the CPS is a prerogative of the system for efficient technological support of the pedagogical process. Detecting and diagnosing mental states of the learners, however, is a challenge to the overall approach, yet a realistic aim (e.g. Schleiger, 2014). The paper focuses on the available knowledge of possible EEG markers of abstraction, attentiveness and memorisation (in some cases combined with eye tracking) related to predicting effective mental and brain processing during the lesson. The role of processing abstraction is emphasised as the learning mechanism, which is given priority over the other mechanisms by the cognitive system. The main markers in focus are P1, N170, Novelty P3, RewP, N400 and P600. The description of the effects is accompanied by analysis of some implications for design of novel educational scenarios in inclusive classes.